Derivative of Inverse
To find the derivative of the inverse of a function, we can use the inverse function theorem
To find the derivative of the inverse of a function, we can use the inverse function theorem. The inverse function theorem states that if a function f(x) has an inverse function f^(-1)(x), and if f'(x) is continuous and nonzero in a neighborhood of a point a, then the derivative of the inverse function f^(-1)(x) at the point b = f(a) is given by:
(f^(-1))'(b) = 1 / f'(a)
This means that the derivative of the inverse function at a point b is equal to the reciprocal of the derivative of the original function at the corresponding point a.
Let’s go through an example to illustrate this concept. Consider the function f(x) = 3x + 2. We want to find the derivative of its inverse function.
Step 1: Find the inverse of f(x):
To find the inverse function, we need to swap the roles of x and y and solve for y. Let’s call the inverse function g(x):
x = 3y + 2
x – 2 = 3y
y = (x – 2) / 3
Therefore, the inverse function of f(x) = 3x + 2 is g(x) = (x – 2) / 3.
Step 2: Find the derivative of f(x):
To find the derivative of f(x), we simply differentiate it with respect to x:
f'(x) = 3
Step 3: Find the derivative of g(x):
Using the inverse function theorem, we know that:
(g^(-1))'(b) = 1 / f'(a)
Since we found that the inverse function g(x) is (x – 2) / 3, we can see that:
(g^(-1))'(b) = 1 / f'(a) = 1 / 3
Therefore, the derivative of the inverse function g(x) = (x – 2) / 3 is:
(g^(-1))'(x) = 1 / 3
To summarize, the derivative of the inverse function is constant and equal to the reciprocal of the derivative of the original function.
More Answers:
Understanding One-to-One Functions: Explained with ExamplesUnderstanding Inverse Functions: A Step-by-Step Guide and Example
Understanding Inverse Symmetry: Definition, Examples, and Mathematical Applications